PENERAPAN METODE MIND MAPPING UNTUK MENINGKATKAN KETERAMPILAN MENULIS CERITA ANAK PADA SISWA DI SEKOLAH DASAR - Fatikha, Mindy (2017)
This research is conducted due to the fact that writing skills of children stories is still low. Based on these problems, then the researcher will sort it out through learning activities by applying the mind mapping learning method to improve the writing skills of children's stories on students in elementary school. The purpose of this research was to describe the implementation of learning and improvement of children's writing skills by applying mind mapping method. The research method used is the classroom action research with adapting the Spiral model by Kemmis and Mc. Taggart and use two cycles. Subject of research is IVB class the grade school year 2016-2017 from one of the elementary school in Sukasari Subdistrict Bandung with subject of research as many as 30 students. Data processing techniques used are calculate the value of the acquisition of children's writing skills in students each cycle, average acquisition classes, and percentage of student learning success. Conclusion in general that use mind mapping methods can improve children's writing skills in students grade IV primary school. While in particular the conclusions of this research are: (1) Implementation of learning method using mind mapping can help students in exploring the ideas that are in his mind, then develop the topic that will be used into subtopics until it becomes a full story. (2) The result of improving children's story writing skills to students in each cycle has increased, with the completeness of children's story writing skills in the first cycle of 47% and in the second cycle of 80% which means the improvement of children's writing skills to students included in the high category.---- Penelitian ini dilatarbelakangi oleh rendahnya keterampilan menulis cerita. Berdasarkan permasalahan tersebut, maka peneliti akan mengatasinya melalui kegiatan pembelajaran dengan menerapkan metode pembelajaran mind mapping untuk meningkatkan keterampilan menulis cerita anak pada siswa di sekolah dasar. Tujuan dari penelitian ini adalah untuk mendeskripsikan pelaksanaan pembelajaran dan peningkatan keterampilan menulis cerita anak dengan menerapkan metode mind mapping. Metode penelitian yang digunakan adalah penelitian tindakan kelas dengan mengadaptasi model Spiral yang dikembangkan oleh Kemmis dan Mc. Taggart dan menggunakan dua siklus. Subjek penelitian adalah siswa kelas IVB tahun ajaran 2016-2017 dari salah satu Sekolah Dasar Negeri di Kecamatan Sukasari Kota Bandung dengan subjek penelitian sebanyak 30 siswa. Teknik pengolahan data yang digunakan adalah menghitung perolehan nilai keterampilan menulis cerita anak pada siswa setiap siklus, perolehan rata-rata kelas, dan persentase ketuntasan belajar siswa. Kesimpulan secara umum bahwa penggunaan metode mind mapping dapat meningkatkan keterampilan menulis cerita anak pada siswa kelas IV sekolah dasar. Sedangkan secara khusus kesimpulan dari penelitian ini adalah: (1) Pelaksanaan pembelajaran dengan menggunakan metode mind mapping dapat membantu siswa dalam menggali ide-ide yang ada dalam pikirannya, kemudian mengembangkan topik yang akan digunakan menjadi subtopik-subtopik hingga menjadi sebuah karangan cerita yang utuh. (2) Hasil peningkatan keterampilan menulis cerita anak pada siswa di setiap siklusnya mengalami peningkatan, dengan perolehan ketuntasan keterampilan menulis cerita anak pada siklus I sebesar 47% dan pada siklus II sebesar 80% yang artinya peningkatan keterampilan menulis cerita anak pada siswa termasuk dalam kategori tinggi.